IL-2-Mediated In Vivo Expansion of Regulatory T Cells Combined with CD154–CD40 Co-Stimulation Blockade but Not CTLA-4 Ig Prolongs Allograft Survival in Naive and Sensitized Mice - Govender, Lerisa; Wyss, Jean-Christophe; Kumar, Rajesh; Pascual, Manuel; Golshayan, Dela (Frontiers in Immunology, 2017)
In recent years, regulatory T cells (Treg)-based immunotherapy has emerged as a promising strategy to promote operational tolerance after solid organ transplantation (SOT). However, a main hurdle for the therapeutic use of Treg in transplantation is their low frequency, particularly in non-lymphopenic hosts. We aimed to expand Treg directly in vivo and determine their efficacy in promoting donor-specific tolerance, using a stringent experimental model. Administration of the IL-2/JES6-1 immune complex at the time of transplantation resulted in significant expansion of donor-specific Treg which suppressed alloreactive T cells. IL-2-mediated Treg expansion in combination with short-term CD154-CD40 co-stimulation blockade, but not CTLA-4 Ig or rapamycin, led to tolerance to MHC-mismatched skin grafts in non-lymphopenic mice, mainly by hindering alloreactive CD8+ effector T cells and the production of alloantibodies. Importantly, this treatment also allowed prolonged survival of allografts in the presence of either donor-specific or cross-reactive memory cells. However, late rejection occurred in sensitized hosts, partly mediated by activated B cells. Overall, these data illustrate the potential but also some important limitations of Treg-based therapy in clinical SOT, as well as the importance of concomitant immunomodulatory strategies in particular in sensitized hosts.